Effect of beta-hydroxy-methylbutyrate on the onset of blood lactate accumulation and O2peak in endurance-trained cyclists - Vukovich, M. D.; Dreifort, G. D. (The Journal of Strength and Conditioning Research, 2001)
The purpose of this study was to determine the effect of -hydroxy -methylbutyrate (HMB) supplementation on maximal oxygen consumption (O2peak) and the onset of blood lactate accumulation (OBLA) in endurance-trained cyclists. Eight cyclists randomly (double blind) completed 3 2-week supplementation periods (HMB, 3g·day1; leucine [LEU], 3g·day1; placebo [CON], 3g·day1) followed by a 2-week washout period. Testing consisted of a graded cycle ergometry test to measure O2peak and OBLA, the O2 at 2 mM blood lactate. O2peak was unaffected by HMB (4.0 ± 1.4%), LEU (1.9 ± 1.3%), and CON (2.6 ± 2.6%). HMB resulted in a greater time to reach O2peak, whereas LEU and CON did not affect this time (HMB, 3.6 ± 1.5 min, LEU, 1.2 ± 1.5 min; CON, 3.6 ± 3.5 min). Lactate accumulation peak was unaffected by supplementation (HMB, 8.1 ± 1.1 mM; LEU, 6.2 ± 0.8 mM; CON, 7.5 ± 1.3 mM). OBLA increased with HMB (9.1 ± 2.4%) and LEU (2.1 ± 1.5%), but not in the CON trial (0.75 ± 2.1%). Blood glucose was significantly greater during the HMB trial compared with the LEU trial. It is concluded that HMB supplementation may have positive affects on performance by increasing the onset of blood lactate accumulation; however, the mechanism is unknown.